ANALISIS PERBANDINGAN SIMULASI LOAD BALANCE MENGGUNAKAN METODE ECMP DAN PCC PADA PENERAPAN KONGESTI MANAJEMEN BANDWIDTH HTB (Studi Kasus: Universitas Kristen Immanuel, Yogyakarta) - Azriel Christian Nurcahyo; Ema Utami; Suwanto Raharjo (Universitas Janabadra, 2019)
Infrastructure and network service is the important things that need to be developed in the campus UKRIM.This is in harmony with the values of both institutions as well as accreditation B overall optimization requires the status of network services to support the learning and performance of the entire civitas academic.During this UKRIM campus networks implementing load balance ECMP and managerial mechanism with a bandwidth of simple queue service of 20 Mbps dedicated and 10 GGC.As a result of congestion often occurs down connection status was at the time interval 1-3 times a month for approximately 5-10 minutes.Responding to this research needed to provide suggestions for the campus network admin UKRIM in providing service load balance as well as managerial bandwidth.This research was conducted on simulation using GNS3 to compare load balance method ECMP and PCC or Per Connection Classifier.As for the HTB used to replace simple queue to minimise wasted bandwidth.Testing on this research using wireshark on a simulated network being built based GNS3.From the test results the comparison using standardization TIPHON obtained that the PCC has advantages compared to the ECMP on condition when a dense network experienced congestion.This is proven by the same throughput rating 100% but the jitter and packet loss is different at PCC have packet loss 15% category medium, the value of jitter 15.69 ms nice category whereas in packet loss value ECMP 58% bad and categories jitter 98.2 ms categories. Keywords: ECMP, GNS3, Per Connection Classifier,Hierarchical Token Bucket.